New low-volume resuscitation solutions containing PEG-20k. Issue 1 (July 2015) - Parrish, Dan; Plant, Valerie; Lindell, Susanne L.; Limkemann, Ashley; Reichstetter, Heather; Aboutanos, Michel; Mangino, Martin J.
<x xml:space="preserve">Abstract</x> BACKGROUND Hypovolemic shock reduces oxygen delivery and compromises energy-dependent cell volume control. Consequent cell swelling compromises microcirculatory flow, which reduces oxygen exchange further. The importance of this mechanism is highlighted by the effectiveness of cell impermeants in low-volume resuscitation (LVR) solutions in acute studies. The objectives of this study were to assess impermeants in survival models and to compare them with commonly used crystalloid solutions. METHODS Adult rats were hemorrhaged to a pressure of 30 mm Hg to 35 mm Hg, held there until the plasma lactate reached 10 mM, and given an LVR solution (5–10% blood volume) with saline alone (control) and saline with various concentrations of polyethylene glycol-20k (PEG-20k), Hextend, or albumin. When lactate again reached 10 mM following LVR, full resuscitation was started with crystalloid and red blood cells. Rats were either euthanized (acute) or allowed to recover (survival). The LVR time, which is the time from the start of the LVR solution until the start of full resuscitation, was measured as was survival and diagnostic laboratory values. In some studies, the capillary oncotic reflection coefficient was determined for PEG-20k to determine its relative impermeant and oncotic effects. RESULTS PEG-20k (10%) significantly increased LVR times relative to saline (eightfold), Hextend, and albumin. Lower amounts of PEG-20k (5%) were also effective but less so than 10% doses. PEG-20k maintained normal arterial pressure during the low-volume state. Survival of a 180-minute LVR time challenge was 0% in saline controls and 100% in rats given PEG-20k as the LVR solution. Surviving rats had normal laboratory values 24 hours later. PEG-20k had an oncotic reflection coefficient of 0.65, which indicates that the molecule is a hybrid cell impermeant with significant oncotic properties. CONCLUSION PEG-20k–based LVR solutions are highly effective for inducing tolerance to the low-volume state and for improving survival.